O uso de treino informatizado para ensinar professores a conduzirem Avaliação de Preferência de Escolha Pareada - Macedo, Viviane Alves de (2021)
Knowing a child's preferences can be an essential strategy to motivate the child to perform tasks in the classroom context. For this, it is important that teachers know how to apply tests to identify these items of preference, especially in children with delayed language development. The present research aims to develop a teaching assessment and test its effectiveness by training teachers in conducting a Paired-Choice Preference Assessment based on Animated Auto-Instructional Video. Two studies were carried out, both developed with Special Education teachers and carried out within a public school, with three participants for each study. In the first, it was tested in a pre and post-test design, in three different conditions (Condition A, Condition B and Condition C), if the Independent Variables (IV), called: 1) Animated Auto-Instructional Video and 2) Instructional Guide (IG), were responsible for modifying the Dependent Variable (DV), called: Conducting a Paired-Choice Preference Assessment. The performance results of the three participants demonstrated the effectiveness of the training performed through Animated Videos. The difficulty of all of them was evidenced in the performance, especially in what concerns the measurement and control of time by means of the stopwatch. The purpose of the second research was to teach teachers through Animated Auto-Instructional Videos (IV), using a multiple baseline design between subjects to measure, in repeated sessions, whether the Dependent Variable (DV), called: Conducting a Paired-Choice Preference Assessment, remains stable throughout the sessions. Three Special Education teachers who work in the Multifunctional Resource Room participated in this study. The repertoire of each subject was evaluated in three baseline sessions, applied before the manipulation of the variables. After the intervention, the repertoires of these participants were again evaluated in three sessions held under the same conditions as the baseline sessions applied previously. The results showed that all participants performed better in the intervention sessions. The performance related to the control and measurement of time using the stopwatch was superior to the performance presented in the first study.